A Novel GPS Antijamming Receiver Based on Noncircularity. (14th December 2009) - Xian-Ning, Chen; Wan, Qun; Wan-Lin, Yang
Abstract : We present a novel antijamming global position system (GPS) receiver that relies on the unique noncircularity of the GPS signal. Since the GPS signal is BPSK modulated, it is a noncircular signal while most interferers are circular signals. The proposed receiver utilizes this circular difference property to excise interferences while preserve the GPS signals. It is shown that the proposed receiver is a blind receiver that does not require any angular information of the satellites.